Will tobacco price increases lead more people who smoke to vape? The results from a discrete choice experiment amongst U.S. adults - Gilda Zarate-Gonzalez; Paul Brown; Linda D. Cameron; Anna V. Song (BMC, 2023)
Abstract Objective To understand the extent to which people who smoke, people who vape and nonsmokers would switch between smoking cigarettes and vaping in response to policies (price increases, restrictions on nicotine, places, and information on addictiveness and/or health risks) aimed at decreasing tobacco use by people who smoke and vaping by nonsmokers. Design A total of 525 adults aged 18 to 88 years completed a discrete choice survey of 16 choices between two smoking/vaping alternatives. Analysis was conducted using conditional logistic regression for the entire sample and stratified by nonsmokers, people who smoke, and people who vape. Results The results suggest that most people who vape also smoke. Nonsmokers were more favorable to vaping and were concerned about long-term health risks and cost associated with vaping. Marginal analysis suggests that price increases will have only modest success in moving people who smoke to start vaping or encouraging people who vape to vape rather than use cigarettes. Nonsmokers are not very sensitive to price changes but are sensitive to information about health impacts. Conclusions Findings indicate that increasing the price of cigarettes would lead to a limited increase in the probability of people who smoke switch to vaping. The study advances our understanding of the views of current nonsmokers toward cigarettes and vaping, suggesting that price increases and increased knowledge of addiction would likely deter nonsmokers from vaping. Changing the amount of nicotine associated with smoking would increase the probability of vaping slightly and have little impact on nonsmokers or vaping preferences, but the most significant change would come from increasing the perceptions of the risk of smoking.